PENGARUH PENGGUNAAN FINANCIAL TECHNOLOGY TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN SEKTOR PERBANKAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Cantika, Renata Bela; Hariyani, Diyah Santi; Saputra, Arifiansyah (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
This study aims to determine the influence of Financial Technology on bank profitability in terms of the profitability ratio of ROA, ROE, NIM, BOPO before and during the Covid-19 pandemic. Researchers conducted research on 4 conventional banks owned by BUMN, namely Bank Mandiri, BNI, BTN, and BRI for the period of financial statements before the Covid-19 pandemic in 2018-2019 and financial statements during the Covid-19 pandemic, namely 2020-2021. The population of this study is banking sector companies listed on the Indonesia Stock Exchange as many as 4 state-owned companies, namely Bank Mandiri, BNI, BTN and BRI that have implemented or adopted FinTech services from 2018-2021. The sampling technique carried out by the researchers used purposive sampling. The data collection technique in this study is the documentation method. The data analysis techniques used in this study are Descriptive Statistical Analysis, Classical Assumption Test, and Paired Sample t-Test. The results showed that there were differences in ROA, ROE, and NIM at Bank Mandiri, while BOPO had no differences. In Bank BNI, BTN, and BTN variables ROA, ROE, NIM, and BOPO there is no difference. Key words : Financial Technology, Profitability, Conventional Bank